Caregiver-reported social impacts in down syndrome regression disorder - Katherine N. Chow; Lilia Kazerooni; Maeve C. Lucas; Samuel T. Otey; Mariam M. Yousuf; Ruth Brown; Eileen A. Quinn; Jonathan D. Santoro (PLoS ONE, 2026)
Background Down Syndrome Regression Disorder (DSRD) is an acute neurocognitive regression in individuals with Down syndrome (DS), causing a profound loss of acquired skills. DSRD increases demands on caregivers, to sleep disturbances, financial distress, and negative impacts on caregiver-reported social connections and perceived social support. The goal of this study was to characterize the caregiver-reported impacts of DSRD on social relationships by comparing their experiences to those of caregivers of individuals with DS and other neurological disorders (DSN). Design/methods This is a narrative burden-of-care study, not a network study. Using cross-sectional study design, caregivers of individuals with DSRD (n = 228) and DSN (n = 137) were recruited from a neurology clinic and a DSRD Facebook support group. Participants completed the DSRD Caregiver Distress Survey (CDS), which included four qualitative, open-ended questions focused on self-perception of adult friendships, social relationship impact, spouse/partner impact, and perceived shrinkage of social world. Responses were analyzed using thematic coding; resulting theme frequencies summarize caregiver-reported perceptions and narratives and do not represent objectively measured social network structure. Results In the DSRD cohort, a high-level overview revealed that 65.66% of responses reported a negative impact on adult friendships, while 71.21% reported a negative impact on social relationships. A negative impact on spouse/partner relationships was reported in 51.53% of responses, and a perceived shrinkage of social world was found in 52.82%. Caregivers in the DSRD group were significantly more likely to report “Social Withdrawal and Isolation” (43.2% vs. 17.9%, p = 0.006), “Loss of Community Participation and/or Support” (16.7% vs 4.5%, p = 0.043) and a “Perceived Enduring Loss of Social Connections” (35.3% vs. 8.7%, p = 0.002) compared to the DSN group. Conclusions This study’s findings reveal a significant and complex process of perceived social disengagement among caregivers describing social withdrawal and loss of social connections that they experienced as enduring. The results emphasize the need for early interventions that address the individual’s needs but also address the caregiver’s social and mental health to prevent perceived long-term social isolation.